Pengembangan Arsitektur Bisnis Sekolah Menggunakan Analisis Semantik - Fitri, Eka Sifatul; Mukaromah, Anisatul; Wahyunigsih, Risky Aprilia; Yaqin, Muhammad Ainul (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2020)
Education in Indonesia must have standards in accordance with the provisions of Badan Standar Nasional Pendidikan to ensure the quality of education. Standar Nasional Pendidikan (SNP) is the education system criteria in Indonesia. SNP is as a reference for curriculum development, education staff, infrastructure, management and financing. SNP is useful for basic planning, implementation, and supervision of education in realizing national education for create an integrated system, methods needed in planning, managing and managing information systems called Enterprise Architecture. Development of enterprise architecture is modeled by the TOGAF (Open Group Architecture Framework) method that is Business Architecture phase. The research used in this Business Architecture is Bottom-Up, which starts the research from the bottom to the up starting from the Standard Operating Procedure (SOP), grouping Job Descriptions using the TF-IDF algorithm, until create an Organizational Structure.